Optimizing the East African Community's Medicines Regulatory Harmonization initiative in 2020-2022: A Roadmap for the Future. - Mawien Arik; Emmanuel Bamenyekanye; Adam Fimbo; Joseph Kabatende; Agnes Sitta Kijo; Burhani Simai; Fred Siyoi; Samvel Azatyan; Aggrey Ambali; Emer Cooke; Jane H Mashingia; John Patrick Mwesigye; et al. (PLoS Medicine, 2020)
Margareth Ndomondo-Sigonda outlines future challenges for the East African Medicines Regulatory Harmonization initiative.